O Aeródromo de Santa Maria (RS) e a sua relação com a atuação brasileira na região do Prata durante a Segunda Guerra Mundial (1939-1945) - Cabral, Thiago Noschang (2025)
This dissertation investigates the geopolitical motivations surrounding the Santa Maria Aerodrome in 1944. The object is chronologically situated during Brazil's "Estado Novo" period and the Second World War (1939-1945) internationally. For this purpose, the study is linked to the Fronteiras, Política e Sociedade of the Programa de Pós-Graduação em História (PPGH), integrated into the Grupo de Pesquisa CNPq/UFSM História Platina, as it seeks to understand the Santa Maria aerodrome as a result of its strategic position in relation to state borders in the Platine Region. The analysis considers the border as a multidimensional locus of historical influence (social, economic, cultural, and, with greater emphasis, political-military). From this perspective, the research was based on the ontological conceptions of the History of International Relations, in order to address the aerodrome's creation and function in the local, national, and international dimensions. Through the construction of the "state of the art," we gained clarity on the following questions that guided this dissertation: what motivations linked to the world conflict led to Santa Maria, an inland city in Rio Grande do Sul, being chosen to host an aerodrome? And how can this theme be a focus for analyzing Brazilian participation in the conflict and its relationship with neighboring countries? The justification for this investigation lies in expanding the perception of how the episode was treated in the related research found, demonstrating the connection of Santa Maria's local reality with the national and international scopes, for which the theoretical conceptualizations of 1930s geopolitics serve as a guiding thread. Methodologically, the investigation consists of a bibliographic research, seeking to locate documentary evidence through previous research that demonstrates the importance of studying the Santa Maria Aerodrome. Heuristically, the search for evidence was carried out by surveying and processing data through the cross-referencing of sources. The documentary evidence found included telegrammes, memoranda, letters, periodicals, and reports from Brazil, Argentina, and the United States. In the end, we concluded that the Aerodrome project unveils a larger-scale plot involving Brazil, Argentina, and the United States in the context of World War II, in which Santa Maria had its role as a military hub reinforced, demonstrating the relationship between the local and the global. This research was supported by a CAPES/DS grant.